PENGARUH PEMBINAAN GURU AL-ISLAM KEMUHAMMADIYAHAN TERHADAP AKHLAK PESERTA DIDIK DI SMK MUHAMMADIYAH 1 PADANG - Ilham, Apri Candra, Ilpi Zukdi, (Menara Ilmu, 2018)
Morals are aspect that must get special attention among human beings, one thatdistinguishes humans and other creatures is morals, so closely morally attached to the human self inparticular. Seeing the reality at this time in particular the child's personality has been too fardeviated from the teachings of religion, all because of influenced by unfavorable environment,causing child behavior becomes impolite and not good, especially at school and at home, this iswhat should be balanced in a way how the role of a teacher, especially the subjects of Al-IslamKemuhammadiyahan so that later children can change morality is not good to be good morals. Thisstudy aims to determine the influence of Al-Islam Kemuhammadiyah teachers guidance on theMorals of Students in the Secondary School Kejuruaan Muhammadiyah 1 Padang. This type ofresearch is descriptive quantitative.Kata Kunci : Pembinaan, Akhlak